2016
DOI: 10.1186/s12917-016-0922-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the early dynamics of the 2014 porcine epidemic diarrhea virus (PEDV) outbreak in Ontario using the incidence decay and exponential adjustment (IDEA) model

Abstract: BackgroundThe United States swine industry was first confronted with porcine epidemic diarrhea virus (PEDV) in 2013. In young pigs, the virus is highly pathogenic and the associated morbidity and mortality has a significant negative impact on the swine industry. We have applied the IDEA model to better understand the 2014 PEDV outbreak in Ontario, Canada. Using our simple, 2-parameter IDEA model, we have evaluated the early epidemic dynamics of PEDV on Ontario swine farms.ResultsWe estimated the best-fit R0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Another study on estimating inter-farm R 0 for PED in Canada used IDEA model, which has been used for projecting epidemic process of ebola 5,6) and Middle East respiratory syndrome coronavirus (MERS) 13) infections in human populations. The structure of IDEA model for PED is simple and has only two parameters : fixed generation interval and control effect 7) . It successfully showed the change of control effect over time, but did not describe mechanic transmission process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on estimating inter-farm R 0 for PED in Canada used IDEA model, which has been used for projecting epidemic process of ebola 5,6) and Middle East respiratory syndrome coronavirus (MERS) 13) infections in human populations. The structure of IDEA model for PED is simple and has only two parameters : fixed generation interval and control effect 7) . It successfully showed the change of control effect over time, but did not describe mechanic transmission process.…”
Section: Discussionmentioning
confidence: 99%
“…Although commonly applied at the individual level, R 0 is also useful for examining animal health at the farm level. Only one study on the farm level R 0 for PED has been reported from Canada 7) , which used the incidence decay and exponential adjustment (IDEA) model. At the animal level, a study in Japan 17) used a compartment model for understanding within-farm PED dynamics, without focusing on the estimation of R 0 .…”
Section: Introductionmentioning
confidence: 99%
“…As truck sharing is a common source of disease transmission in animal shipment networks (Dee, Deen, Burns, Douthit, & Pijoan, ; Greer, Spence, & Gardner, ; Lowe et al, ), we construct two‐mode binary contact networks (location‐to‐truck networks) to investigate truck sharing practices in windows of days, weeks, months and for the entire study period. Each unique location and each unique truck are nodes, and edges are defined as the sharing of trucks by locations.…”
Section: Methodsmentioning
confidence: 99%
“…Withdrawal of the SDPP containing feed did not alter the rate of new PEDV outbreaks. Greer, Spence, and Gardner () reported the cumulative incidence for the Ontario PEDV outbreaks before and after the withdrawal of SDPP containing feed from the market. There was no change in increase in cumulative incidence rate after withdrawal of the SDPP‐containing feed (Figure ).…”
Section: Retrospective Review Of Epidemiology From 2014 Canadian Pedvmentioning
confidence: 99%
“…Cumulative incidence data for the Ontario porcine epidemic diarrhoea virus outbreak in 2014. Cases occurring prior to 20 February 2014 (dashed line) are assumed to be the result of a point source exposure through swine feed with cases occurring after 20 February 2014 being the result of direct farm‐to‐farm transmission (adapted from Greer et al, )…”
Section: Retrospective Review Of Epidemiology From 2014 Canadian Pedvmentioning
confidence: 99%